A randomised control trial of low glycaemic index carbohydrate diet versus no dietary intervention in the prevention of recurrence of macrosomia - Foley Michael; Mahony Rhona; Walsh Jennifer; Mc Auliffe Fionnuala (BMC, 2010)
Abstract Background Maternal weight and maternal weight gain during pregnancy exert a significant influence on infant birth weight and the incidence of macrosomia. Fetal macrosomia is associated with an increase in both adverse obstetric and neonatal outcome, and also confers a future risk of childhood obesity. Studies have shown that a low glycaemic diet is associated with lower birth weights, however these studies have been small and not randomised <abbrgrp>12</abbrgrp>. Fetal macrosomia recurs in a second pregnancy in one third of women, and maternal weight influences this recurrence risk <abbrgrp>3</abbrgrp>. Methods/Design We propose a randomised control trial of low glycaemic index carbohydrate diet vs. no dietary intervention in the prevention of recurrence of fetal macrosomia. Secundigravid women whose first baby was macrosomic, defined as a birth weight greater than 4000 g will be recruited at their first antenatal visit. Patients will be randomised into two arms, a control arm which will receive no dietary intervention and a diet arm which will be commenced on a low glycaemic index diet. The primary outcome measure will be the mean birth weight centiles and ponderal indices in each group. Discussion Altering the source of maternal dietary carbohydrate may prove to be valuable in the management of pregnancies where there has been a history of fetal macrosomia. Fetal macrosomia recurs in a second pregnancy in one third of women. This randomised control trial will investigate whether or not a low glycaemic index diet can affect this recurrence risk. Current Controlled Trials Registration Number ISRCTN54392969